Implementation of the Eazy Passport Office of Immigration Class I TPI Tanjung Perak at the University of Muhammadiyah Gresik - Edwinarta, Caesar Demas (Universitas Brawijaya, 2020)
Immigration is everything related to the process of entering and leaving people into Indonesian territory and enforcing the law for the sake of upholding the country's sovereignty. Passport services as one of the main aspects of immigration have an important role, especially in the midst of a pandemic. The Directorate General of Immigration on its way issued an Eazy Passport service policy as a solution to the reduction in the number of passport issuances and Non-Tax State Revenue (PNBP) generated by the Immigration Office. Research on the implementation of the Eazy Passport service by taking a case study at the TPI Tanjung Perak Immigration Office Class I which carries out services at the University of Muhammadiyah Gresik. The research analysis uses public policy theory with the concept of policy implementation combined with mixed research methods. The initial hypothesis states that the implementation of the Eazy Passport service is less effective and requires analysis of several aspects in its implementation. The results of research that show the ineffectiveness of the Eazy Passport service at the University of Muhammadiyah Gresik in increasing the number of passport and PNBP issuances at the TPI Tanjung Perak Immigration Class I, provide suggestions to make the procedure for the minimum number of applicants more flexible with 25-30 people per day. It is hoped that with a smaller minimum number of applicants, it will be able to increase the intensity of the number of agencies in joining the Eazy Passport service. The increasing number of agencies will directly increase the number of passport issuances and PNBP which are the main objectives of implementing the Eazy Passport service.